Is the Extent of the Preoperative Air‐Bone Gap an Indictor of Potential Success in Stapedectomy?. (2nd September 2014) - Lavy, Jeremy; Huins, Charlie; Hall, Andrew; Whitcroft, Katherine; Khalil, Sherif
Abstract : Objectives: (1) Could preoperative air‐bone gap (ABG) magnitude act as a predictor of postoperative outcome in patients undergoing stapedectomy for otosclerosis? (2) If this were to occur, is it frequency specific? Methods: Retrospective case series from January 2010 to December 2012 in a tertiary London teaching hospital. Intervention: Laser stapedectomy using Smart Nitinol stapes prosthesis. Main outcome measure: Audiometric. Retrospective analysis comparing preoperative and postoperative air‐bone gap in 302 patients undergoing stapedectomy. Patients were stratified into subgroups according to their preoperative ABG and this was compared to their postoperative result of air‐bone closure. In addition, for each commonly tested frequency (0.5, 1, 2, 3, 4 kHz) the preoperative and postoperative air‐bone gap were analyzed in order to ascertain whether the preoperative ABG could act as a predictor. Having not passed normality testing, Wilcoxon matched paired signed rank test and Spearman rank coefficient were used for analysis. Results: Throughout the statistical analysis, preoperative ABG correlated most strongly with net difference in postoperative ABG ( P <. 0001). For each commonly tested frequency assessed this demonstrated a "very strong" positive correlation. As such, the greater the preoperative ABG, the greater the closure obtained through stapedectomy in this series. Conclusions: In performing stapedectomy for otosclerosis, our series suggested the preoperative ABG may have a role in preoperative patient counseling and consent but is unable to predict success in stapedectomy surgery.